GPI-AP: Unraveling a New Class of Malignancy Mediators and Potential Immunotherapy Targets - Hussein, Nada H.; Amin, Nada S.; El Tayebi, Hend M. (Frontiers in Oncology, 2020)
With millions of cases diagnosed annually and high economic burden to cover expensive costs, cancer is one of the most difficult diseases to treat due to late diagnosis and severe adverse effects from conventional therapy. This creates an urgent need to find new targets for early diagnosis and therapy. Progress in research revealed the key steps of carcinogenesis. They are called cancer hallmarks. Zooming in, cancer hallmarks are characterized by ligands binding to their cognate receptor and so triggering signaling cascade within cell to make response for stimulus. Accordingly, understanding membrane topology is vital. In this review, we shall discuss one type of transmembrane proteins: Glycosyl phosphatidyl inositol-Anchored Proteins (GPI-APs), with specific emphasis on those involved in tumor cells by evading immune surveillance and future applications for diagnosis and immune targeted therapy.